Modelling of one-bit Arithmetic Logic Circuit using silicon micro-ring resonator. Issue 1 (1st September 2022) - Hossain, M; Singh, M P; Rakshit, J K
Abstract: All-optical technology overcomes the problems that arise in traditional digital circuits such as speed limitation, energy consumption and size. In this manuscript, we have implemented a one-bit arithmetic logic circuit employing all-optical silicon micro-ring resonator that utilizes the advantages over other all-optical techniques. The Arithmetic logic circuit is the core component of ultra-fast combinational circuits. The proposed arithmetic logic circuit is validated through MATLAB at about 260 Gbps. Performance of our design has been investigated by numerical simulation. The critical parameters of MRR are optimized on the basis of performance metrics.